EXTINGUISHING MASS COMBUSTION IN COAL BEDS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A cheap and effective method of combating spontaneous combustion of coal seams in open mines is considered. The design of the installation for extinguishing coal seams is proposed, which does not require large costs and works automatically; one person is required to maintain the installation.